Research-based rehabilitation of the lower back - Rogers, R. G. (Strength and Conditioning Journal, 2006)
This article presents an exercise-based approach to the management of chronic lower back pain. The exercises are selected based on specific functional deficits that have been identified in the population with low back pain. This information can be used by strength and conditioning professionals who wish to provide an efficient, research-supported approach to this common malady.